Ultrahigh-temperature-resistant heavy anti-corrosion coating applied to petroleum refining equipment, preparation method and coating method of ultrahigh-temperature-resistant heavy anti-corrosion coating
Through the composite preparation of soluble solution solution solution of the solid polycal polyxane resin in the liquid polycis silicane, prepare a high -temperature resistant and heavy anticorrosive coating, solve the insufficient temperature resistance limit of existing coatings in high temperature environments The problem realizes the effective anti -corrosion and durability of petroleum refining equipment.
Patent Information
- Application Number
- CN202411519251.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-24
AI Technical Summary
The existing polysilazane coatings have insufficient temperature resistance in high temperature environments, and the application of solid polymer polysilazane resins in the coating field has not been reported by patents, so they cannot effectively deal with the harsh environment of petroleum refining equipment.
The composite preparation method of liquid polyetraxane hypocritical resin and solid polymer silicane resin solution solution is used to prepare an ultra -high temperature and heavy anticorrosive coating through a specific mass ratio and process process. This coating contains a liquid polyckal chunane hydrological resin, solid polymer polysiliconane resin solution solution, nanoscolus containment powder, dispersant, defoaming agent, anti -sediment, and organic solvents.
This coating has good salt -resistant corrosion performance, acid -alkali corrosion performance, high temperature resistance, friction resistance, high toughness and high hardness performance, can significantly improve the anticorrosive performance and durability of petroleum refining equipment, and reduce the cost of material.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the field of polymer coatings, and in particular to an ultra-high temperature resistant heavy-duty anti-corrosion coating used in petroleum refining equipment, a preparation method and a coating method thereof. Background Art
[0002] As a new type of polymer material, polysilazane can adhere closely to smooth substrates such as metals, minerals, glass, ceramics and organic materials. It can be converted into ceramic phases such as silicon oxygen, silicon nitrogen, silicon carbon nitrogen under specific high temperature conditions to cope with thermal environments above 800°C; it can also be cured under medium and low temperature conditions to cope with thermal environments of 200-800°C. It is an excellent coating resin material. After the polysilazane resin is cured into a film, its coating has excellent properties such as ultra-high hardness, hydrophobicity and oleophobicity, high corrosion resistance, and ultra-high heat resistance. Therefore, it has broad application prospects in the fields of hydrophobicity, corrosion resistance and antifouling, temperature resistance, high-temperature ceramics and non-stick coatings.
[0003] At present, the polysilazane coatings on the market all use liquid polysilazane oligomer resin as the film-forming material. The coating has the advantages of being hydrophobic, high temperature resistant, and having good bonding strength, but its temperature resistance limit is still relatively low. After the liquid polysilazane oligomer resin is cured, its temperature resistance limit is 1000°C, and it is still unable to withstand scenes exceeding this temperature; the relevant patent reports a high-temperature resistant polysilazane coating, which is matched with a high-temperature resistant pigment. The coating does not change color, crack, or fall off under 700-1200°C. At the same time, after the liquid polysilazane oligomer is formed into a film, the coating is not flexible enough and there is a risk of cracking. The temperature resistance limit of solid polymer polysilazane can reach 1350°C. Through special element modification, its temperature resistance limit can reach 1500-1800°C, which greatly expands the scope of use in thermal field environments. Alternatively, by modifying the polymer, its curing conditions can be reduced to room temperature, reducing the construction curing conditions; related patents report a boron-doped high-temperature resistant polysilazane resin, which adds high-temperature resistant fillers such as hexagonal boron nitride and zirconium oxide to prepare a room-temperature self-curing coating that can withstand temperatures exceeding 800°C, greatly reducing the application threshold. Solid polymer polysilazane appears as solid powder or solid particles at room temperature, and its molecular weight reaches 100,000-200,000. Since solid polymer polysilazane is easily soluble in a variety of organic solvents, it is convenient for its application in the field of coatings, but there are currently no patent reports on the application of solid polymer polysilazane resins.
[0004] During the service process, petroleum refining equipment faces harsh environmental conditions, such as raw materials, catalysts, products, water vapor corrosion, high temperature, sunlight, etc., so the material requirements for the equipment are also harsh. For example, important reaction equipment and separation equipment require the use of titanium alloy steel or more corrosion-resistant and heat-resistant steel. The material cost is huge, and the loss caused by corrosion is even greater. Therefore, it has always caused huge cost pressure on enterprises. Solid polymer polysilazane resin has excellent adhesion to steel. The coating prepared by it can withstand neutral salt spray for more than 5000 hours, acid salt spray for more than 480 hours, artificial climate aging for more than 5000 hours, and temperature resistance for more than 1350℃ after curing, which is enough to cope with the harsh environment of petroleum refining equipment. Therefore, the development of an ultra-high temperature resistant heavy-duty anti-corrosion coating with solid polymer polysilazane resin as the main film-forming substance has positive practical significance for reducing the material cost of petroleum refining equipment, and is also of great significance for import substitution. Summary of the invention
[0005] In order to solve the above technical problems, the present application provides an ultra-high temperature resistant heavy-duty anti-corrosion coating for petroleum refining equipment, a preparation method and a coating method thereof.
[0006] The present application provides an ultra-high temperature resistant heavy-duty anti-corrosion coating for petroleum refining equipment, a preparation method and a coating method thereof, which adopt the following technical solutions: In the first aspect, the present application provides an ultra-high temperature resistant heavy-duty anti-corrosion coating for petroleum refining equipment, which adopts the following technical solution: An ultra-high temperature resistant heavy-duty anti-corrosion coating for petroleum refining equipment includes the following components in percentage by weight: Liquid polysilazane oligomer resin 10%-40%, organic solvent 10%-50%, nano pigment filler powder 10%-30%, dispersant 4%-6%, defoamer 1%-3%, anti-precipitation agent 2%-5%, and the balance is solid high molecular weight polysilazane resin solution.
[0007] By adopting the above technical scheme, the polysilazane oligomer resin has the properties of high temperature resistance, corrosion resistance, oxidation resistance, etc., and has strong mechanical properties and thermal stability. The solid polymer polysilazane resin is composed of elements such as silicon, nitrogen, and carbon. It has both the heat resistance and weather resistance of Si elements and the oxidation resistance, aging resistance and chemical stability of N elements. It has excellent temperature resistance and chemical stability, and can make the coating have high temperature resistance. The anti-corrosion coating is prepared by mixing the components according to the above mass ratio. The coating has good salt spray corrosion resistance and good acid and alkali corrosion resistance. At the same time, it can give the product the properties of high temperature resistance, friction resistance, high toughness and high hardness, so as to improve the comprehensive performance of the product.
[0008] Preferably, the liquid polysilazane oligomer resin is obtained by blending liquid methyl hydrogen polysilazane oligomer and liquid vinyl polysilazane oligomer, and the mass ratio of the liquid methyl hydrogen polysilazane oligomer to the liquid vinyl polysilazane oligomer is (9-7):(1-3).
[0009] By adopting the above technical scheme, the methyl groups contained in methyl polysilazane can increase the branching degree of its molecular chain, thereby improving its solubility performance. Vinyl polysilazane oligomer has good thermal stability, mechanical properties, high temperature resistance and corrosion resistance. The combination of the two improves the compatibility of the system, and can make the polysilazane oligomer resin dispersed evenly and stably in the coating, thereby improving the stability of the coating.
[0010] Preferably, the liquid methyl hydrogen polysilazane oligomer is prepared by the following method: Methylhydrogendichlorosilane is added to an organic solvent, and a low-temperature ammonolysis reaction is carried out in an ammonia environment to obtain a mixture of methylhydrogensilazane oligomers and by-product ammonium chloride, and then the ammonium chloride solid is filtered out, and the organic solvent in the filtered solution is separated by pressure distillation to obtain methylhydrogenpolysilazane oligomers.
[0011] By adopting the above technical scheme, methylhydrogendichlorosilane is ammonolyzed and the by-products are removed to obtain methylhydrogenpolysilazane oligomers, which can effectively improve the purity and strength of methylhydrogenpolysilazane. At the same time, the processing technology is simple, which can further improve the comprehensive performance of the coating.
[0012] Preferably, the liquid vinyl polysilazane oligomer is prepared by the following method: Methylvinyldichlorosilane is added to an organic solvent, and a low-temperature ammonolysis reaction is carried out in an ammonia environment to obtain a mixture of vinylsilazane oligomers and by-product ammonium chloride. The ammonium chloride solid is then filtered out, and the organic solvent in the solution is separated by reduced pressure distillation to obtain vinylpolysilazane oligomers.
[0013] By adopting the above technical solution, after the by-products are removed by ammonolysis of methylvinyldichlorosilane, the purity of the vinyl polysilazane oligomer is improved, and it has good thermal stability and mechanical properties, which effectively improves the overall comprehensive performance of the coating.
[0014] Preferably, the solid polymer polysilazane resin solution is prepared by the following method: A methyl hydrogen polysilazane oligomer and a vinyl polysilazane oligomer are mixed and added to a reactor containing an organic solvent, a curing agent is added to the reactor, and a solid polymer polysilazane resin is obtained by high temperature polymerization. The solid polymer polysilazane resin obtained by high temperature polymerization is added to an organic solvent, and a solid polymer polysilazane resin solution is obtained after soaking; the mass ratio between the methyl hydrogen polysilazane oligomer and the vinyl polysilazane oligomer is (9-7):(1-3).
[0015] By adopting the above technical solution, the stability of the solid polymer polysilazane resin solution obtained by composite configuration after limiting the mass ratio of methyl hydrogen polysilazane oligomer and vinyl polysilazane oligomer is further improved.
[0016] Preferably, the organic solvent includes any two or more mixtures of alkanes, aromatic hydrocarbons, halogenated hydrocarbons, ether solvents, ester solvents, ether ester solvents, and ketone solvents.
[0017] Preferably, the nano pigment filler powder includes any one or more mixtures of nano-scale silicon carbide, silicon nitride, titanium nitride, boron nitride, zirconium oxide, copper chrome black, cobalt black, titanium white, titanium chrome brown, chromium oxide green, aluminum oxide, talc, barium sulfate, and silica fume; the dispersant includes any one or more mixtures of BYK-161, BYK-P104S, EFKA-4330, and SOLSPERSE 32500; the defoamer includes any one or more mixtures of BYK-077, BYK-088, and BYK-141; the anti-precipitation agent includes any one or more mixtures of fumed silica and inorganic bentonite.
[0018] In the second aspect, the present application provides a method for preparing an ultra-high temperature resistant heavy-duty anti-corrosion coating for petroleum refining equipment, which adopts the following technical scheme: A method for preparing an ultra-high temperature resistant heavy-duty anti-corrosion coating for petroleum refining equipment comprises the following steps: S1. Add the solid polymer polysilazane solution into a double-layer barrel and stir it with a high-speed disperser. Add the liquid polysilazane oligomer, dispersant, defoamer, anti-precipitant, nano pigment filler powder and organic solvent into the double-layer barrel in the required proportion. Use a disperser to stir and disperse at a speed of 1800 rpm for 1-2 hours. S2. Replace the dispersion disc with a grinding disc, add zirconium beads and open the low-temperature constant temperature bath to circulate and cool the double-layer barrel. At the same time, start grinding at a speed of 2000 rpm. After the material is ground for 4h-8h, separate the zirconium beads and the coating through a filter cloth to obtain an anti-corrosion coating.
[0019] In a third aspect, the present application provides a coating method for an ultra-high temperature resistant heavy-duty anti-corrosion coating for petroleum refining equipment, which adopts the following technical solution: A coating method of an ultra-high temperature resistant heavy-duty anti-corrosion coating for petroleum refining equipment comprises the following steps: (1) The workpiece surface is derusted, degreased, washed, and dried in sequence to complete the pretreatment; (2) Applying the coating evenly to the pre-treated workpiece; (3) Drying and curing the coating on the workpiece to obtain an anti-corrosion coating and complete the coating.
[0020] In the step (3), the coating is carried out by any one of spraying, brushing and dipping.
[0021] Preferably, the drying temperature in step (1) is 20-80°C, the drying time is 0.5-2h, and the thickness of the anti-corrosion coating is 10-30 μm; the curing temperature in step (3) is 130-600°C, and the curing time is 2h.
[0022] By adopting the above technical solution, the coating conditions are preferably within the above range, which can further improve the stability of the anti-corrosion coating obtained after coating.
[0023] In summary, the present application includes at least one of the following beneficial technical effects: 1. The anti-corrosion coating is prepared by compounding liquid polysilazane oligomer resin, solid polymer polysilazane resin solution and other materials. The polysilazane oligomer resin has good mechanical properties and thermal stability. The solid polymer polysilazane resin is composed of silicon, nitrogen, carbon and other elements, and has the properties of heat resistance, weather resistance, oxidation resistance, aging resistance and chemical stability. The coating obtained by compounding the components has good salt spray corrosion resistance and acid and alkali corrosion resistance. At the same time, it can give the product the properties of high temperature resistance, friction resistance, high toughness and high hardness, so as to improve the comprehensive performance of the product; 2. After the by-products are removed from the ammonolysis of methylhydrogendichlorosilane, methylhydrogenpolysilazane oligomers are obtained, which can effectively improve the purity and strength of methylhydrogenpolysilazane. After the by-products are removed from the ammonolysis of methylvinyldichlorosilane, the purity of the vinylpolysilazane oligomer is improved, and it has good thermal stability and mechanical properties. The solid polymer polysilazane resin solution prepared by the combination of the two further improves the stability of the coating. DETAILED DESCRIPTION
[0024] The present application is further described in detail below with reference to the embodiments: Example 1 Solid polymer polysilazane resin solution: Methyl hydrogen polysilazane oligomer (purchased from Anhui Mingyi Silicon Industry Co., Ltd.) and vinyl polysilazane oligomer (CAS No.: 503590-70-3) were mixed in a mass ratio of 9:1 and added to a reactor filled with an organic solvent. A curing agent was added to the reactor and high-temperature polymerization was performed to obtain a solid polymer polysilazane resin. The solid polymer polysilazane resin obtained by high-temperature polymerization was mixed with the organic solvent in a mass ratio of 1:1 and sealed, and a solid polymer polysilazane resin solution was obtained after standing for 24 hours; wherein the organic solvent was an isoalkane (CAS No.: 68551-20-2).
[0025] Preparation of liquid methyl hydrogen polysilazane oligomer: Methylhydrogendichlorosilane (CAS No.: 75-54-7) is added to an organic solvent, and a low-temperature ammonolysis reaction is carried out in an ammonia environment to obtain a mixture of methylhydrogensilazane oligomers and by-product ammonium chloride, and then the ammonium chloride solid is filtered out, and the organic solvent in the filtered solution is separated by pressure distillation to obtain methylhydrogenpolysilazane oligomers; wherein the organic solvent is xylene (CAS No.: 1330-20-7).
[0026] Preparation of liquid vinyl polysilazane oligomer: Methylvinyldichlorosilane (CAS No.: 124-70-9) is added to an organic solvent, and a low-temperature ammonolysis reaction is carried out in an ammonia environment to obtain a mixture of vinylsilazane oligomers and by-product ammonium chloride, and then the ammonium chloride solid is filtered out, and the organic solvent in the solution is separated by reduced pressure distillation to obtain vinyl polysilazane oligomers; wherein the organic solvent is butyl acetate.
[0027] Preparation of liquid polysilazane oligomer resin: The methyl hydrogen polysilazane oligomer and the vinyl polysilazane oligomer were mixed in a mass ratio of 9:1 to prepare a liquid polysilazane oligomer resin.
[0028] Applied in the preparation of ultra-high temperature resistant heavy-duty anti-corrosion coatings for petroleum refining equipment: S1. Add the solid polymer polysilazane solution into a double-layer barrel and stir with a high-speed disperser. Add the liquid polysilazane oligomer resin, dispersant BYK-161, dispersant BYK-088, anti-precipitation agent inorganic bentonite, nano pigment filler powder boron nitride nano powder, nano pigment filler powder silicon nitride micro powder, nano pigment filler powder zirconium oxide nano powder, nano pigment filler powder silicon carbide micro powder, organic solvent xylene, organic solvent n-hexane and organic solvent propylene glycol methyl ether acetate (CAS No.: 108-65-6) into the solid polymer polysilazane resin solution. Use a disperser to continuously disperse at a speed of 1800r / min for 1h to obtain a mixed slurry. In the mixed slurry, 10wt% of the liquid polysilazane oligomer resin, BYK-161, BYK-088, and BYK-088 are added. 4wt%, BYK-0881wt%, inorganic bentonite 2wt%, boron nitride nanopowder 2wt%, silicon nitride micropowder 4wt%, zirconium oxide nanopowder 2wt%, silicon carbide micropowder 4wt%, xylene 20wt%, n-hexane 9wt%, propylene glycol methyl ether acetate 20wt%, and the rest are solid polymer polysilazane resin dissolved liquid and inevitable impurities.
[0029] S2. Replace the dispersion disc with a grinding disc, add zirconium beads to the double-layer barrel for grinding and open the low-temperature constant temperature bath to circulate and cool the double-layer barrel. At the same time, the disperser starts grinding at a speed of 2000 rpm. After grinding the mixed slurry for 4 hours, use a 200-mesh filter cloth to separate the zirconium beads and the coating to obtain the anti-corrosion coating.
[0030] Application of ultra-high temperature resistant heavy-duty anti-corrosion coatings for petroleum refining equipment: (1) The workpiece surface is derusted, degreased, washed, and dried in sequence to complete the pretreatment; (2) using a spraying method to evenly spray the prepared anti-corrosion coating on the surface of the pre-treated workpiece, with a spraying thickness of 20-30 μm; (3) Drying and curing the coating on the workpiece, the drying temperature is 25°C, the drying time is 1 hour, the curing temperature is 250°C, and the curing time is 2 hours; after drying and curing, an anti-corrosion coating is obtained and the coating is completed.
[0031] Example 2 Preparation of solid polymer polysilazane resin solution: Methyl hydrogen polysilazane oligomer and vinyl polysilazane oligomer are mixed in a mass ratio of 7:3 and added to a reactor filled with an organic solvent, a curing agent is added to the reactor, and high-temperature polymerization is performed to obtain a solid polymer polysilazane resin, and the solid polymer polysilazane resin obtained by high-temperature polymerization is mixed with an organic solvent in a mass ratio of 1:1 and sealed, and a solid polymer polysilazane resin solution is obtained after standing for 24 hours; wherein the organic solvent is propylene glycol diacetate.
[0032] Preparation of liquid methyl hydrogen polysilazane oligomer: Methylhydrogendichlorosilane is added to an organic solvent, and a low-temperature ammonolysis reaction is carried out in an ammonia environment to obtain a mixture of methylhydrogensilazane oligomers and by-product ammonium chloride, and then the ammonium chloride solid is filtered out, and the organic solvent in the filtered solution is separated by pressurized distillation to obtain methylhydrogenpolysilazane oligomers; wherein the organic solvent is propylene glycol methyl ether acetate.
[0033] Preparation of liquid vinyl polysilazane oligomer: Methylvinyldichlorosilane is added to an organic solvent, and a low-temperature ammonolysis reaction is carried out in an ammonia environment to obtain a mixture of vinylsilazane oligomers and by-product ammonium chloride, and then the ammonium chloride solid is filtered out, and the organic solvent in the solution is separated by reduced pressure distillation to obtain vinylpolysilazane oligomers; wherein the organic solvent is methyl isobutyl ketone (CAS No.: 108-10-1).
[0034] Preparation of liquid polysilazane oligomer resin: The methyl hydrogen polysilazane oligomer and the vinyl polysilazane oligomer were mixed in a mass ratio of 8:2 to prepare a liquid polysilazane oligomer resin.
[0035] Applied in the preparation of ultra-high temperature resistant heavy-duty anti-corrosion coatings for petroleum refining equipment: S1. Add solid polymer polysilazane solution into a double-layer barrel and stir with a high-speed disperser. Add liquid polysilazane oligomer resin, dispersant EFKA-4330, dispersant BYK-077, anti-precipitation agent fumed silica, nano pigment filler powder boron nitride nano powder, nano pigment filler powder silicon nitride micro powder, nano pigment filler powder zirconium oxide nano powder, nano pigment filler powder silicon carbide micro powder, organic solvent xylene and organic solvent propylene glycol methyl ether acetate into solid polymer polysilazane resin solution. Use a disperser to continuously disperse at a speed of 1800r / min for 2h to obtain a mixed slurry. In the mixed slurry, liquid polysilazane oligomer resin 20wt%, EFKA-4330 4wt%, BYK-077 1wt%, fumed silica 2wt%, boron nitride nanopowder 5wt%, silicon nitride micropowder 2wt%, zirconium oxide nanopowder 2wt%, silicon carbide micropowder 2wt%, xylene 16wt%, propylene glycol methyl ether acetate 15wt%, and the rest are solid polymer polysilazane resin solution and inevitable impurities.
[0036] S2. Replace the dispersion disc with a grinding disc, grind the zirconium beads added to the double-layer barrel and open the low-temperature constant temperature bath to circulate and cool the double-layer barrel. At the same time, the disperser starts grinding at a speed of 2000 rpm. Grind the mixed slurry for 6 hours, and use a 200-mesh filter cloth to separate the zirconium beads and the coating to obtain the anti-corrosion coating.
[0037] Application of ultra-high temperature resistant heavy-duty anti-corrosion coatings for petroleum refining equipment: (1) The workpiece surface is derusted, degreased, washed, and dried in sequence to complete the pretreatment; (2) using a spraying method to evenly spray the prepared anti-corrosion coating on the surface of the pre-treated workpiece, with a spraying thickness of 20-30 μm; (3) Drying and curing the coating on the workpiece, the drying temperature is 60°C, the drying time is 1 hour, the curing temperature is 400°C, and the curing time is 2 hours; after drying and curing, an anti-corrosion coating is obtained and the coating is completed.
[0038] Example 3 Preparation of solid polymer polysilazane resin solution: Methyl hydrogen polysilazane oligomer and vinyl polysilazane oligomer are mixed in a mass ratio of 8:2 and added to a reactor filled with an organic solvent, a curing agent is added to the reactor, and high-temperature polymerization is performed to obtain a solid polymer polysilazane resin, and the solid polymer polysilazane resin obtained by high-temperature polymerization is mixed with an organic solvent in a mass ratio of 1:1 and sealed, and a solid polymer polysilazane resin solution is obtained after standing for 24 hours; wherein the solvent is n-hexane.
[0039] Preparation of liquid methyl hydrogen polysilazane oligomer: Methylhydrogendichlorosilane is added to an organic solvent, and a low-temperature ammonolysis reaction is carried out in an ammonia environment to obtain a mixture of methylhydrogensilazane oligomers and by-product ammonium chloride, and then the ammonium chloride solid is filtered out, and the organic solvent in the filtered solution is separated by pressurized distillation to obtain methylhydrogenpolysilazane oligomers; wherein the organic solvent is n-hexane.
[0040] Preparation of liquid vinyl polysilazane oligomer: Methylvinyldichlorosilane is added to an organic solvent, and a low-temperature ammonolysis reaction is carried out in an ammonia environment to obtain a mixture of vinylsilazane oligomers and by-product ammonium chloride, and then the ammonium chloride solid is filtered out, and the organic solvent in the solution is separated by reduced pressure distillation to obtain vinylpolysilazane oligomers; wherein the organic solvent is n-hexane.
[0041] Preparation of liquid polysilazane oligomer resin: The methyl hydrogen polysilazane oligomer and the vinyl polysilazane oligomer were mixed in a mass ratio of 7:3 to prepare a liquid polysilazane oligomer resin.
[0042] Applied in the preparation of ultra-high temperature resistant heavy-duty anti-corrosion coatings for petroleum refining equipment: S1. Add solid polymer polysilazane dissolved liquid into a double-layer barrel and stir with a high-speed disperser. Add 10wt% of liquid polysilazane oligomer resin, dispersant BYK-P104S, dispersant BYK-141, anti-precipitation agent fumed silica, nano pigment filler powder boron nitride nano powder, nano pigment filler powder silicon nitride micro powder, nano pigment filler powder zirconium oxide nano powder, nano pigment filler powder silicon carbide micro powder, organic solvent xylene and organic solvent propylene glycol methyl ether acetate into the solid polymer polysilazane resin dissolved liquid. Use a disperser to continuously disperse at a speed of 1800r / min for 2h to obtain a mixed slurry. In the mixed slurry, 10wt% of liquid polysilazane oligomer resin, 4wt% of BYK-P104S, and 10wt% of BYK-141 are added. 1wt%, fumed silica 2wt%, boron nitride nanopowder 6wt%, silicon nitride micropowder 3wt%, zirconium oxide nanopowder 3wt%, silicon carbide micropowder 3wt%, xylene 9wt%, propylene glycol methyl ether acetate 8wt%, added to the solid polymer polysilazane resin solution S2. Replace the dispersion disc with a grinding disc, add zirconium beads to the double-layer barrel for grinding and open the low-temperature constant temperature bath to circulate and cool the double-layer barrel. At the same time, the disperser starts grinding at a speed of 2000 rpm. After grinding the mixed slurry for 6 hours, use a 200-mesh filter cloth to separate the zirconium beads and the coating to obtain the anti-corrosion coating.
[0043] Application of ultra-high temperature resistant heavy-duty anti-corrosion coatings for petroleum refining equipment: (1) The workpiece surface is derusted, degreased, washed, and dried in sequence to complete the pretreatment; (2) using a spraying method to evenly spray the prepared anti-corrosion coating on the surface of the pre-treated workpiece, with a spraying thickness of 20-30 μm; (3) Drying and curing the coating on the workpiece, the drying temperature is 60°C, the drying time is 1 hour, the curing temperature is 400°C, and the curing time is 2 hours; after drying and curing, an anti-corrosion coating is obtained and the coating is completed.
[0044] Performance testing The coating color, solid content, dry film thickness, pencil hardness, adhesion and neutral salt spray resistance of the samples of Examples 1-3 were tested, and the test results were filled in Table 1; among them, the solid content test was based on "GB / T 1725-2007" as the testing standard, the dry film thickness was based on "GB / T 13452.2-2008" as the testing standard, the pencil hardness was based on "GB / T 6739-2022" as the testing standard, the adhesion was based on "GB / T 9286-2021" as the testing standard, the corrosion resistance was based on "GB / T 1771-2007" as the testing standard, the temperature resistance was based on "GB / T 1735-2009" as the testing standard, and the aging resistance was based on "GB / T 1865-2009" as the testing standard.
[0045] Table 1 Test results of sample performance Combined with Table 1, it can be seen that the sample coatings prepared in Examples 1-3 have good performance, indicating that the heavy-duty anti-corrosion coating prepared in this application has good comprehensive properties such as high temperature resistance and corrosion resistance.
[0046] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. An ultra-high temperature resistant heavy-duty anti-corrosion coating for petroleum refining equipment, characterized by: The composition comprises the following weight percentages: Liquid polysilazane oligomer resin 10%-40%, organic solvent 10%-50%, nano pigment filler powder 10%-30%, dispersant 4%-6%, defoamer 1%-3%, anti-precipitation agent 2%-5%, the balance is solid high molecular weight polysilazane resin solution.
2. The ultra-high temperature resistant heavy-duty anti-corrosion coating for petroleum refining equipment according to claim 1, characterized in that: The liquid polysilazane oligomer resin is obtained by blending liquid methyl hydrogen polysilazane oligomer and liquid vinyl polysilazane oligomer, and the mass ratio between the liquid methyl hydrogen polysilazane oligomer and the liquid vinyl polysilazane oligomer is (9-7):(1-3).
3. The ultra-high temperature resistant heavy-duty anti-corrosion coating for petroleum refining equipment according to claim 2, characterized in that: The liquid methyl hydrogen polysilazane oligomer is prepared by the following method: Methylhydrogendichlorosilane is added to an organic solvent, and a low-temperature ammonolysis reaction is carried out in an ammonia environment to obtain a mixture of methylhydrogensilazane oligomers and by-product ammonium chloride, and then the ammonium chloride solid is filtered out, and the organic solvent in the filtered solution is separated by pressure distillation to obtain methylhydrogenpolysilazane oligomers.
4. The ultra-high temperature resistant heavy-duty anti-corrosion coating for petroleum refining equipment according to claim 2, characterized in that: The liquid vinyl polysilazane oligomer is prepared by the following method: Methylvinyldichlorosilane is added to an organic solvent, and a low-temperature ammonolysis reaction is carried out in an ammonia environment to obtain a mixture of vinylsilazane oligomers and by-product ammonium chloride. The ammonium chloride solid is then filtered out, and the organic solvent in the solution is separated by reduced pressure distillation to obtain vinylpolysilazane oligomers.
5. The ultra-high temperature resistant heavy-duty anti-corrosion coating for petroleum refining equipment according to claim 1, characterized in that: The solid polymer polysilazane resin solution is prepared by the following method: A methyl hydrogen polysilazane oligomer and a vinyl polysilazane oligomer are mixed and added to a reactor containing an organic solvent, a curing agent is added to the reactor, and a solid polymer polysilazane resin is obtained by high temperature polymerization. The solid polymer polysilazane resin obtained by high temperature polymerization is added to an organic solvent, and a solid polymer polysilazane resin solution is obtained after soaking; the mass ratio between the methyl hydrogen polysilazane oligomer and the vinyl polysilazane oligomer is (9-7):(1-3).
6. The ultra-high temperature resistant heavy-duty anti-corrosion coating for petroleum refining equipment according to any one of claims 1 to 5, characterized in that: The organic solvent includes any one of alkanes, aromatic hydrocarbons, halogenated hydrocarbons, ether solvents, ester solvents, ether ester solvents, and ketone solvents, or a mixture of two or more thereof.
7. The ultra-high temperature resistant heavy-duty anti-corrosion coating for petroleum refining equipment according to claim 1, characterized in that: The nano pigment filler powder includes any one or more mixtures of nano-scale silicon carbide, silicon nitride, titanium nitride, boron nitride, zirconium oxide, copper chrome black, cobalt black, titanium white, titanium chrome brown, chromium oxide green, aluminum oxide, talc, barium sulfate, and silica fume; the dispersant includes any one or more mixtures of BYK-161, BYK-P104S, EFKA-4330, and SOLSPERSE 32500; the defoamer includes any one or more mixtures of BYK-077, BYK-088, and BYK-141; the anti-precipitation agent includes any one or more mixtures of fumed silica and inorganic bentonite.
8. A method for preparing the ultra-high temperature resistant heavy-duty anti-corrosion coating for petroleum refining equipment according to any one of claims 1 to 7, characterized in that: The steps include: S1. Add the solid polymer polysilazane solution into a double-layer barrel and stir it with a high-speed disperser. Add the liquid polysilazane oligomer, dispersant, defoamer, anti-precipitant, nano pigment filler powder and organic solvent into the double-layer barrel in the required proportion. Use a disperser to stir and disperse at a speed of 1800 rpm for 1-2 hours. S2. Replace the dispersion disc with a grinding disc, add zirconium beads and open the low-temperature constant temperature bath to circulate and cool the double-layer barrel. At the same time, start grinding at a speed of 2000 rpm. After the material is ground for 4h-8h, separate the zirconium beads and the coating through a filter cloth to obtain an anti-corrosion coating.
9. A coating method for the ultra-high temperature resistant heavy-duty anti-corrosion coating for petroleum refining equipment according to claim 8, characterized in that: The steps include: (1) The workpiece surface is derusted, degreased, washed and dried in sequence to complete the pretreatment; (2) Apply the coating evenly to the workpiece after pretreatment; (3) Dry and cure the coating on the workpiece to obtain an ultra-high temperature resistant anti-corrosion coating, completing the coating.
10. The coating in step (3) is carried out by any one of spraying, brushing and dipping.
11. The coating method of the ultra-high temperature resistant heavy-duty anti-corrosion coating for petroleum refining equipment according to claim 9, characterized in that: In the step (1), the drying temperature is 20-80°C, the drying time is 0.5-2h, and the thickness of the anti-corrosion coating is 10-30 μm; in the step (3), the curing temperature is 130-600°C, and the curing time is 2h.
Citation Information
Patent Citations
Coating composition containing polysilazane
CN102153951A
Synthesis method of high-silicon-hydrogen polysilazane and prepared single-component ceramic coating
CN115636941A
Crosslinkers for silazane polymers
EP0808863A2
Forming method for ceramic heat resistant insulative coating film
JP1993081926A
Method for increasing molecular weight of polysilazane, high-molecular-weight polysilazane, and heat-resistant insulated wire coated with the same and baked
JP1994136130A